Adolescent use of combined hormonal contraception and peak bone mineral density accrual: A meta‐analysis of international prospective controlled studies. (10th February 2019) - Goshtasebi, Azita; Subotic Brajic, Tatjana; Scholes, Delia; Beres Lederer Goldberg, Tamara; Berenson, Abbey; Prior, Jerilynn C.
Summary: Objective: Many women use combined hormonal contraceptives (CHC) during adolescence during which they are accruing peak areal bone mineral density (BMD) that relates to lifetime fracture risk. To build BMD requires formation with which CHC‐related exogenous oestrogen may interfere. We compared peak BMD accrual in adolescents using and not using CHC. Design/Participants: We performed literature searches for prospective published peer‐reviewed articles providing 12‐ to 24‐month BMD change in adolescent (12‐ to 19‐year‐old) women using CHC vs CHC‐unexposed control women. Methods: Meta‐analyses used random‐effects models to assess BMD change rate at lumbar spine (LS) and other sites in adolescent CHC users vs CHC nonusers. Results: Literature searches yielded 84 publications of which nine were eligible. Adolescent‐only data were sought from cohorts with wider age inclusions. The 12‐month LS meta‐analysis with eight paired comparisons in 1535 adolescents showed a weighted mean BMD difference of −0.02 (95% confidence interval [CI]: −0.05 to 0.00) g/cm 2 in CHC‐exposed adolescents ( P  = 0.04). The 24‐month LS meta‐analysis with five paired comparisons in 885 adolescents showed a highly significant weighted mean BMD difference of −0.02 (95% CI: −0.03 to −0.01) g/cm 2 in CHC‐exposed adolescents ( P  = 0.0006). Heterogeneities by I 2 were 96% and 85%, respectively. Insufficient data for other bone sites precluded quantitative analysis. Conclusion: Given that adolescent exposure to CHC appears to be increasing, this evidence for potential impairment of peak spinal BMD accrual is of concern and suggests a potential public health problem. Randomized controlled trial data are needed to determine CHC effects on adolescent bone health.